A compassion-based treatment for couples with the female partner suffering from current depressive disorder: A randomized-controlled trial - Aguilar-Raab, Corina; Winter, Friederike; Warth, Marco; Stoffel, Martin; Moessner, Markus; Hernández, Cristóbal; Pace, Thaddeus; Harrison, Timothy; Negi, Lobsang Tenzin; Jarczok, Marc N.; Ditzen, Beate (Journal of affective disorders, 2023)
Background - Studies have shown that depression and interpersonal relationships are interdependently connected and that including the intimate partner in treatment for depression has beneficial effects. Given evidence that compassion is both an interpersonal quality and a promising treatment target, the goal of this study was to examine the effects of a compassion-based, contemplative treatment for couples employing a multi-method approach for evaluation. - Methods - In a pre-post-follow-up design, n = 53 different-sex couples including women with current depression were randomly assigned to a 10-week-long CBCT®-fC (Cognitively-Based Compassion Training/intervention for couples) or treatment-as-usual (TAU) condition. Multi-level linear regression models and post-hoc contrasts were calculated to determine changes in depressive symptoms, mindfulness and self-compassion, interpersonal functioning and neuroendocrine markers collected during a partnership appreciation task (PAT) in the laboratory before and after CBCT-fC treatment. - Results - While CBCT-fC led to a comparable decrease of depressive symptoms as TAU, the training specifically increased self-compassion and mindfulness versus TAU. Interestingly, interpersonal functioning did not improve, which was also reflected in participants' preferred self-focus in-between-session practices, instead of practices with interpersonal focus. There were no group-specific changes in psychobiological stress-marker reactivity. - Conclusions - CBCT-fC was effective in decreasing current depressive symptomatology and increasing mindfulness, and self-compassion. Especially the motivation to participate, such as improving interpersonal functioning, should be addressed and intrinsic motives of the partners to be involved. In highly burdened individuals, self-regulation may need to be improved before co-regulation can be addressed, which would requiring longer treatments. Facilitating factors for engaging in the practice between-sessions seem meaningful.